Perspektiewe vir ’n normatiewe politiek: die boodskap van die Instituut vir Reformatoriese Studie (IRS) tydens ’n stormagtige staatkundige tydperk (1976-1996) in Suid-Afrika - Walt, Barend Johannes van der (Koers, 2008)
Perspectives for a normative politics: the message of the Institute for Reformational Studies (IRS) during a turbulent constitutional period (1976-1996) in South Africa This essay has a two-fold aim. It firstly investigates the political message of the IRS during the period of approximately 1976 to 1996 as well as its relevance for the contemporary political dispensation in South Africa. Secondly, for the purpose of future research, it provides the results of bibliographical research about IRS publications on politics and related issues. The first (systematic) part starts with the worldviewish foundations for a Christian perspective on politics. Then the value of a structural analysis of the state is explained in detail. Finally a few guidelines for political action are given. In the second (bibliographical) section the material is arranged (in order to follow the historical development) in a chronological order and the different IRS series are given (in view of further research) in separate bibliographies.